Produção mais limpa (P+L) na etapa de alvenaria em condomínio vertical: estudo de caso - Prado, Raquel Nazário da Rosa (Universidade do Vale do Rio dos Sinos, 2021)
The civil construction industry is one of the sectors responsible for the large consumption of natural raw materials, it is also one of the largest generators of solid waste. It is estimated that the sector is responsible for about 60% of urban solid waste generated in the world. The raw materials used in the construction processes are mostly non-renewable, which makes the environmental impact more significant. In light of the above, this work explored the application of the tools of the Cleaner Production Program in a vertical residential condominium built in structural masonry, in the masonry execution process. The method used was the case study. For this purpose, the existing processes were analyzed through a detailed description and identified the raw material consuming activities as well as the waste generating activities during the production process. Subsequently, improvements were proposed in the processes based on the P+L priority hierarchy, in order to mitigate the generated waste. The present work identified that the execution of the structural masonry consumes 3.3kWh/m² of electricity and 0.02 m³/m² of drinking water, with 0.009m³/m² of water becoming effluent due to the washing process of materials and equipment. The consumption of mortar was 0.0175m³/m² of masonry built, however 18% of this became construction waste. Concrete block consumption was 13.85uni./m², however 5% of these became waste due to the lack of planning for their distribution in the slab under construction. In the grouting activity there was a consumption of 1.33m³/m², with 7.7% of which become waste due to the inefficiency of the inspection window seals. In view of this, 5 improvement opportunities were suggested, based on the P+L priority hierarchy, aimed at minimizing waste at the source, with 02 opportunities at level 01, 02 opportunities at level 02 and 01 opportunity at level 01 and 02.
Keywords: Produção mais limpa; Resíduos da construção; Construção civil; Cleaner production; Construction waste; Civil construction; ACCNPQ::Engenharias::Engenharia Civil